The impact of challenge and hindrance stressors on newcomers’ organizational socialization: A moderated-mediation model - Tang, Yi; Zhang, Zhijun; Wu, Shengnan; Zhou, Ju (Frontiers in Psychology, 2022)
The importance of work stress on newcomers' organizational socialization has been a topic of substantial interest. However, the impact mechanism of different stressors on newcomers' organizational socialization is still in the early stages of theory development. This study, based on the theory of the dual work stress model, explored how to challenge stressors and hindrance stressors impact newcomers' organizational socialization via the mediation of job crafting. Based on the empirical data from 247 newcomers, we found that challenge stressors positively affected newcomers' organizational socialization; on the contrary, hindrance stressors would result in negative influences. In addition, leader-member exchange enhanced the positive effect of challenge stressors on newcomers' job crafting and further moderated the indirect influence of challenge stressors on newcomers' organizational socialization via job crafting. These findings provide a practical guide for organizations to apply stress management and promote newcomers' socialization.